Pengaruh Kepemimpinan, Disiplin, dan Motivasi Kerja Terhadap Kinerja Karyawandi Stikes Wira Medika Bali - Silvia Ni Nyoman Sintari; Anak Agung Dewi Larantika; Anak Agung Gede Raka (Universitas Warmadewa, 2022)
STIKesWiraMedika Bali as a private higher education, has made efforts to obtain quality health workers who are capable of realizing change, growth and renewal as well as optimal health services for the entire community. This was done because he realized that as an institution in the field of education there were many competitors in its business activities, thus making STIKesWiraMedika Bali continue to improve the performance of its employees. Performance appraisal in the 2019 period shows that there are several aspects of the assessment that have decreased the performance of the employees.This research is a quantitative research. The number of samples was 92 peoples with the sampling technique used was Non Probality Sampling, namely total sampling. The data collection used questionnaires and data analysis was performed using the multiple linear regression method. The results showed that leadership has an influence on the performance of employees, the t value is 2,062 with a probability value (sig value) of 0,042. Motivation has an influence on employee performance, the t value is 5,019 with a probability value (sig value) of 0,000. Work discipline has an influence on the performance of employees with a t value of 2,008 with a probability value (sig value) of 0,048. Leadership, Work Motivation, Work Discipline jointly influence the performance of employees with a calculated F value of 13,427 with a probability value (sig value) of 0,000.